2018
DOI: 10.33233/fb.v18i5.661
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre fatores antropométricos e o desempenho de escolares em tarefas de equilí­brio

Abstract: Objetivo: Este estudo objetivou avaliar a associação entre fatores antropométricos e o desempenho de escolares em tarefas motoras de equilíbrio. Método: Participaram do estudo 284 escolares, com oito anos de idade, matriculados em escolas públicas do Município de São José-SC. Para avaliar equilíbrio foram utilizadas as tarefas especificas das baterias MABC-2 e KTK; a base de apoio plantar foi avaliada por meio de um pedigráfo (PODO tech) e o índice de massa corporal (peso/estatura²) foi avaliado por uma balanç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A previous study that used the KTK on 627 children aged from 5 to 6 years found no differences in motor skills between males and females [29]. However, another study showed that boys had 1.72 more chance of motor discoordination than girls when walking in the cross bars [30]. Lopes et al [31] evaluated 7175 overweight/obese and eutrophic children aged from 6 to 14 years with the KTK and concluded that regardless of gender, overweight/ obese children had lower motor development scores when compared to the eutrophic group.…”
Section: Resultsmentioning
confidence: 94%
“…A previous study that used the KTK on 627 children aged from 5 to 6 years found no differences in motor skills between males and females [29]. However, another study showed that boys had 1.72 more chance of motor discoordination than girls when walking in the cross bars [30]. Lopes et al [31] evaluated 7175 overweight/obese and eutrophic children aged from 6 to 14 years with the KTK and concluded that regardless of gender, overweight/ obese children had lower motor development scores when compared to the eutrophic group.…”
Section: Resultsmentioning
confidence: 94%